IMPLEMENTATION OF A COMBINATION OF FERNET ENCRYPTION AND LSB STEGANOGRAPHY IN AN IMAGE-BASED INFORMATION SECURITY SYSTEM - Jadiaman Parhusip; Muhammad Arifin Ilham; Rinaldi Rizwar; Arya Bima Mohammad Heriansyah; Raydamar Rizkyaka Riyadi (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
Information security is an essential aspect in the digital era, where data exchange is highly vulnerable to misuse. The combination of cryptography and steganography provides dual protection by securing message confidentiality and concealing its presence. This study implements the Fernet Encryption algorithm for data encryption and the Least Significant Bit (LSB) technique for embedding encrypted messages into digital images. The system is developed using Python with the cryptography, Pillow, and NumPy libraries. In this study, the cover medium is a randomly generated noise image, chosen to ensure sufficient embedding capacity, making visual distortion irrelevant to the analysis. Experimental results show that the encrypted token can be successfully embedded, extracted, and decrypted using the correct key. These findings demonstrate that the combination of Fernet and LSB serves as an effective proof-of-concept for layered security mechanisms in digital image media, with potential for further development using natural images for practical steganography applications.